Evaluation of translocation of black bears involved in human–bear conflicts in South‐central Colorado. (3rd March 2015) - Alldredge, Mat W.; Walsh, Daniel P.; Sweanor, Linda L.; Davies, Robert B.; Trujillo, Al
ABSTRACT From 1995 to 1997, black bears (Ursus americanus) involved in conflicts with humans in southeastern Colorado, USA, were radiocollared, translocated, and monitored by the Colorado Division of Wildlife to evaluate translocation as a management tool for problem black bears. Specific objectives were to 1) determine postrelease movement patterns of relocated black bears, and 2) estimate cumulative incidence and survival functions. Subadults did not move as far after translocation as adults and less frequently oriented toward the capture site (29% of subad vs. 51% of ad). No subadults returned to the vicinity of capture, whereas 33% of adults did. We used a cause‐specific hazards model with a constant age effect across the cause‐specific hazards to estimate annual survival rate for translocated adult bears (0.50, 95% credible interval CI = 0.36–0.65) and for subadult bears (0.28, 95% CI = 0.12–0.48). The annual probability of dying due to repeat conflict behavior was slightly lower (0.22 [95% CI = 0.13–0.33] and 0.32 [95% CI = 0.19–0.47]) for adults and subadults, respectively, compared with nonconflict mortalities (0.28 [95% CI = 0.17–0.40] and 0.40 [95% CI = 0.25–0.56]). Based on bears that were not involved in known repeat human–bear conflicts, translocation success was 0.64 (95% CI = 0.49–0.78) and 0.58 (95% CI = 0.42–0.73) for adults and subadults, respectively. Translocation of problem bears had mixed success relative to repeat nuisance activity in Colorado, but should remain a viable management option. Managers should make decisions on the appropriateness of translocation based on the characteristics of the bear, identification of an adequate release site, potential effect of the translocation on the release‐site bear population, and other available options. © 2015 The Wildlife Society.